Reconsidering Archaeological Fieldwork Exploring On-Site Relationships Between Theory and Practice - Cobb, Hannah.; Cobb, Hannah.; Harris, Oliver J. T.; Harris, Oliver J. T.; Jones, Cara.; Jones, Cara.; Richardson, Philip.; Richardson, Philip. (Springer New York : Imprint: Springer, 2012)
Digging, recording, and writing are the three main processes that archaeologists undertake to analyze a site, yet the relationships between these processes is rarely considered critically. Reconsidering Archaeological Fieldwork asserts that each of these processes involve active interpretation. When a group of archaeologists works together to reconstruct  the past, at a particular time, at a particular site, their field methods and interpretations affect the final analysis and constantly test the boundaries of what is subjective and what is objective.   This volume explores the important nature of the relationship between fieldwork, analysis, and interpretation. Containing contributions from a diverse group of archaeologists, both academic and professional, from Europe and the Americas, it critically assesses accepted practices in field archaeology, and provides thoughtful and innovative analysis of these procedures. By combining the experiences of both academic and professional archaeologists, Reconsidering Archaeological Fieldwork highlights key differences and key similarities in their concerns, theories, and techniques. This volume will incite discussion on fundamental questions for all archaeologists, both old and new to the field.